Math Notes Exercise 6.1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Chapter 6

SEQUENCES AND SERIES

SEQUENCE

om
A sequence is a function whose domain is a subset of the set of natural numbers. First
term of the sequence is usually denoted by a1, second by a2, third by a3 and similarly nth term
of the sequence is denoted by an.

.c
EXERCISE 6.1
Q.1 Write the first four terms of the following sequences, if
(i)
(iii)
an = 2n – 3
an = (– 1)n (2n – 3)
n
(ii)
(iv)
ty
an = (– 1)n n2
an = 3n – 5
1
ci
(v) an = (vi) an = n
2n + 1 2
(vii) an – an – 1 = n + 2, a1 = 2
em

(viii) an = n an – 1, a1 = 1
(ix) an = (n + 1) an – 1, a1 = 1
1
(x) an =
a + (n – 1) d
le

Solution:
(i) an = 2n – 3
ta

Given
an = 2n – 3
n = 1, 2, 3, 4
n = 1  a1 = 2 (1) – 3 = 2 – 3 = – 1
n = 2  a2 = 2 (2) – 3 = 4 – 3 = 1
n = 3  a3 = 2 (3) – 3 = 6 – 3 = 3
n = 4  a4 = 2 (4) – 3 = 8 – 3 = 5
So the required terms are – 1, 1, 3, 5.
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 394 Mathematics (Part-I)

(ii) an = (– 1)n n2
Given sequence
an = (– 1)n n2
Put n = 1, 2, 3, 4
n = 1  a1 = (– 1) (1)2 = – 1
n = 2  a2 = (– 1)2 (2)2 = 4
n = 3  a3 = (– 1)3 (3)2 = (– 1) (9) = – 9
n = 4  a4 = (– 1)4 (4)2 = (1) (16) = 16
So required terms are – 1, 4, – 9, 16

om
(iii) an = (– 1)n (2n – 3)
Given sequence
an = (– 1)n (2n – 3)

.c
Put n = 1, 2, 3, 4
n = 1  a1 = (– 1)1 (2 (1) – 3) = – (2 – 3) = – (– 1) = 1
n = 2 
n = 3 
ty
a2 = (– 1)2 (2 (2) – 3) = 4 – 3 = 1
a3 = (– 1)3 (2 (3) – 3) = (– 1) (6 – 3) = – 3
ci
n = 4  a4 = (– 1)4 (2 (4) – 3) = 8 – 3 = 5
So required terms are 1, 1, – 3, 5
em

(iv) an = 3n – 5
Given sequence
an = 3n – 5
le

Put n = 1, 2, 3, 4, 5
n = 1  a1 = 3(1) – 5 = 3 – 5 = – 2
ta

n = 2  a2 = 3 (2) – 5 = 6 – 5 = 1
n = 3  a3 = 3 (3) – 5 = 9 – 5 = 4
n = 4  a4 = 3 (4) – 5 = 12 – 5 = 7
so the required terms are – 2, 1, 4, 7
n
(v) an =
2n + 1
Given sequence
n
an =
2n + 1
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 395 Mathematics (Part-I)

Put n = 1, 2, 3, 4
1 1 1
n = 1  a1 = = =
2(1) + 1 2+1 3
2 2 2
n = 2  a2 = = =
2(2) + 1 4+1 5
3 3 3
n = 3  a3 =
2 (3) + 1 6 + 1 = 7
4 4 4
n = 4  a4 = = =
2(4) + 1 8+1 9

om
1 2 3 4
so the required terms are   
3 5 7 9
1
(vi) an =
2n

.c
Given sequence
1
an =
2n
Put n = 1, 2, 3, 4
1 1
ty
n = 1 
ci
a1 = = 2
21
1 1
n = 2  a2 = = 4
em

22
1 1
n = 3  a3 = 3 =
8
2
1 1
n = 4 
le

a4 = 4 =
2 16
1 1 1 1
so the required terms are 2  4  8  16
ta

(vii) an – an – 1 = n + 2, a1 = 2
Given
an – an – 1 = n + 2, (1) a1 = 2
Put n = 2 in (1)
a2 – a1 + 2 + 2
a2 – 2 = 4
a2 = 4 + 2 = 6
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 396 Mathematics (Part-I)

Put n = 3 in (1)
a3 – a2 = 3 + 2
a3 – 6 = 5
a3 = 6 + 5 = 11
Put n = 4 in (1)
a4 – a3 = 4 + 2
a4 – 11 = 6
a4 = 6 + 11 = 17

om
 required terms are 2, 6, 11, 17
(viii) an = n an – 1, a1 = 1
Given

.c
an = n an – 1, (1) a1 = 1
Put n = 2 in (1)
a2 = 2a1 = 2 (1) = 2
Put n = 3 in (1)
ty
 a1 = 1
ci
a3 = 3a2 = 3 (2) = 6
Put n = 4 in (1)
em

a4 = 4a3
a4 = 4 (6) = 24
 required terms are 1, 2, 6, 24
le

(ix) an = (n + 1) an – 1, a1 = 1
Given
ta

an = (n + 1) an–1 a1 = 1 (1)
Put n = 2 in (1)
a2 = (2 + 1) a1 = 3a1 = 3 (1) = 3
Put n = 3 in (1)
a3 = (3 + 1) a2 = 4a2 = 4 (3) = 12
Put n = 4 in (1)
a4 = (4 + 1) a3 = 5a3 = 5 (12) = 60
 required terms are 1, 3, 12, 60
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 397 Mathematics (Part-I)

1
(x) an =
a + (n – 1) d
Given
1
an =
a + (n – 1) d
Put n = 1, 2, 3, 4
1 1 1
n = 1  a1 = = =
a + (1 – 1) d a+0 a
1 1
Put n = 2  a2 = =
a + (2 – 1) d a+d

om
1 1
Put n = 3  a3 =
a + (3 – 1) d = a + 2d
1 1
Put n = 4  a4 = =
a + (4 – 1) d a + 3d

.c
Q.2 Find the indicated terms of the following sequences:
(i) 2, 6, 11, 17, ...... a7 (ii) 1, 3, 12, 60, ...... a6

(iii)
(v)
3 5 7
1,    ...... a7
2 4 8
(iv)
1, – 3, 5, – 7, 9, – 11, ...... a8
ty
1, 1, – 3, – 7, ...... a8
ci
Solution:
Given
em

2, 6, 11, 17, ...... a7


from the given sequence, we have
a1 = 2 a2 = 2 + 4 = 6
a3 = 6 + 5 = 11 a4 = 11 + 6 = 17
le

a5 = 17 + 7 = 24 a6 = 24 + 8 = 32
a7 = 32 + 9 = 41
ta

 required term is a7 = 41
(ii) 1, 3, 12, 60, ...... a6
Given
1, 3, 12, 60, ….. a6
from the given sequence, we have
a1 = 1 a2 = 1 x 3 = 3
a3 = 3 x 4 = 12 a4 = 12 x 5 = 60
a5 = 60 x 6 = 360 a6 = 360 x 7 = 2520
so the required term = a6 = 2520.
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 398 Mathematics (Part-I)

3 5 7
(iii) 1,    ...... a7
2 4 8
Given
3 5 7
1,    ...... a7
2 4 8
from the given sequence
1+2 3
a1 = 1 a2 = =
1 (2) 2
3+2 5 5+2 7
a3 = = a4 = =

om
2 (2) 4 4 (2) 8
7+2 9 9+2 11
a5 = = a6 = =
8 (2) 16 16 (2) 32
11 + 2 13
a7 = = 64
32 (2)

.c
13
 required term = a7 = 64

(iv) 1, 1, – 3, 5, – 7, ...... a8
Given
ty
ci
1, 1, – 3, 5, – 7, ...... a8
from the given sequence
em

a1 = 1 a2 = 1
a3 = 1 – 4 = – 3 a4 = 1 + 4 = 5
a5 = – 3 – 4 = – 7 a6 = 5 + 4 = 9
a7 = – 7 – 4 = – 11
le

a8 = 9 + 4 = 13
(v) 1, – 3, 5, – 7, 9, – 11, ...... a8
ta

Given
1, – 3, 5, – 7, 9, – 11, ...... a8
From the given sequence
a1 = 1 a2 = – 3
a3 = 5 a4 = – 7
a5 = 9 a6 = – 11
a7 = 13 a8 = – 15
Hence required term = a8 = – 15

Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 399 Mathematics (Part-I)

Q.3 Find the next two terms of the following sequences.


(i) 7, 9, 12, 16, ...... (ii) 1, 3, 7, 15, 31, ......
(iii) – 1, 2, 12, 40, ...... (iv) 1, – 3, 5, – 7, 9, – 11, ......
Solution:
(i) 7, 9, 12, 16, ......
Given sequence
7, 9, 12, 16, ......
 a1 = 7 a2 = 7 + 2 = 9

om
a3 = 9 + 3 = 12 a4 = 12 + 4 = 16
a5 = 16 + 5 = 21 a6 = 21 + 6 = 27
so next two terms are 21, 27
(ii) 1, 3, 7, 15, 31, .....

.c
Given sequence
1, 3, 7, 15, 31, .....
 a1 = 1
a3 = 3 + 4 = 7
ty
a2 = 1 + 2 = 3
a4 = 7 + 8 = 15
ci
a5 = 15 + 16 = 31 a6 = 31 + 32 = 63
a7 = 63 + 64 = 127
em

so next two terms are 63, 127.


(iii) – 1, 2, 12, 40, ......
Given sequence
– 1, 2, 12, 40, ......
le

a1 = – 1 x – 1 = – 1
a2 = 1 x 2 = 2
ta

a3 = 3 x 4 = 12
a4 = 5 x 8 = 40
a5 = 7 x 16 = 112
a6 = 9 x 32 = 288
 the next two terms of the sequence are 112, 288
(iv) 1, – 3, 5, – 7, 9, – 11, .....
Given sequence
1, – 3, 5, – 7, 9, – 11, .....
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com
[Ch.6] Sequences and Series 400 Mathematics (Part-I)

 a1 = 1
a2 = – 3
a3 = 5
a4 = – 7
a5 = 9
a6 = – 11
a7 = 13
a8 = – 15

om
 next two terms are 12, – 15.
Arithmetic Progression (A. P)
A sequence {an} is an Arithmetic sequence or Arithmetic progression (A.P) if an – an – 1

.c
is the same number for all n  N and n > 1. The difference of two consecutive terms of an A.P
is called common difference and is usually denoted by d. a n = a1 + (n – 1)d is called the nth
term or general term of the A.P.
ty
General form of A.P a1, a1 + d, a1 + 2d, a1 + 3d, …..
EXERCISE 6.2
ci
Q.1 Write the first four terms of the following arithmetic sequence, if
(i) a1 = 5 and other three consecutive terms are 23, 26, 29
em

(ii) a5 = 17 and a9 = 37
(iii) a7 = 7a4 and a10 = 33
Solution:
le

(i) a1 = 5 and other three consecutive terms are 23, 26, 29


As the given sequence is arithmetic sequence so d = 26 – 23 = 3
and a1 = 5 (given)
ta

 a2 = a1 + d = 5 + 3 = 8
a3 = a2 + d = 8 + 3 = 11
a4 = a3 + d = 11 + 3 = 14
 first four terms of the sequence are 5, 8, 11, 14.
(ii) a5 = 17 and a9 = 37
As a5 = 17  a1 + 4d = 17  (1)
a9 = 37  a1 + 8d = 37  (2)
Visit for other book notes, past papers, tests papers and guess papers taleemcity.com

You might also like